Circumstances of hospital admissions in palliative care: A cross-sectional survey of patients admitted to hospital with palliative care needs. (May 2018) - Robinson, Jackie; Gott, Merryn; Frey, Rosemary; Ingleton, Christine
Background: On average, people will experience 2.28 hospital admissions in the last year of life with the likelihood of a hospital admission increasing in the last 2 weeks of life. Reducing hospital admissions has become a focus for high-income countries as they work to manage the financial implications of an ageing population. However, the circumstances by which patients with palliative care needs are admitted to hospital remain poorly understood. Aim: To explore the circumstances of hospital admissions for patients with palliative care needs. Design: Cross-sectional survey design using face-to-face questionnaires. Setting/participants: In total, 116 patients aged >18 years admitted to a tertiary hospital with palliative care needs. Results: Those with a non-cancer diagnosis and those aged over 75 years were less likely to have hospice involved prior to the admission ( x 2 (1, n = 116) = 10.19, p = 0.00). Few patients recognised community services as having a role in enabling them to remain at home. Those with cancer placed a significantly higher priority on receiving information about their illness ( t (114) = 2.03, p = 0.04) and receiving tests and investigations ( t (114) = 2.37, p = 0.02) in hospital. Conclusion: This study has demonstrated the complexity of hospital admissions in palliative care. Further research is needed to explore patient perceptions of care at home and the role of community services to enable them to remain at home. Understanding the motivation to come to hospital in the context of an incurable illness and limited treatment options may help to inform the development of services that can enable better care at home.